Herbarium‐based measurements reliably estimate three functional traits. Issue 10 (18th September 2020) - Perez, Timothy M.; Rodriguez, Jessica; Mason Heberling, J.
Abstract : Premise: The use of functional traits has surged in recent decades, providing new insights ranging from individual plant fitness to ecosystem processes. Global plant trait databases have advanced our understanding of plant functional diversity, but they remain incomplete because of geographic and taxonomic biases. Herbarium specimens may help fill these gaps by providing trait information across space and time. We tested whether herbarium specimen‐derived measurements are reliable estimates of three important, commonly measured functional traits—specific leaf area (SLA), branch wood specific gravity, and leaf thickness. Methods: Leaves and branches were collected from species cultivated at Fairchild Tropical Botanic Garden and Florida International University in Miami, FL, USA. Fresh components of SLA (area), branch wood specific gravity (volume), and leaf thickness were measured following standard trait measurement protocols. We compared these trait values to corresponding measurements using plant tissues dried in a plant press following standard herbarium plant collecting protocols. Results: Herbarium‐derived trait measurements (dried tissues) were highly correlated with those measured using fresh tissues following standard protocols (SLA: R 2 = 0.72–0.97, p < 0.01; wood specific gravity: R 2 = 0.74–0.75, p < 0.01; leaf thickness: R 2 = 0.96, p < 0.01). However, except for leaf thickness, linear model slope or intercept coefficients differed from 1, indicating herbarium‐derived trait measurements may provide biased estimates of fresh traits without the use of correction factors. Conclusions: Herbarium‐derived traits cannot always be used interchangeably with those measured from fresh tissues because of tissue shrinkage. However, herbarium‐derived trait data still have the potential to drastically expand the temporal, geographic, and taxonomic scope of global trait databases.